Food Management System and Satisfaction Level of Students of Pesantren Tebuireng Jombang, East Java (Medico Legal Update, 2020)
Efforts so that a person’s nutritional needs can be obtained optimally is by holding a food that is managedby applying various scientific disciplines. This study aims to analyze the food delivery system and the levelof satisfaction of students in Tebuireng Islamic Boarding School in Jombang, East Java. This research wasobservational with a cross-sectional study design. Samples taken are students who live and or boardingat Tebuireng Islamic Boarding School in Jombang, East Java, with a total of 303 people from the class2 population. Samples were taken using total sampling. Data collection is done by providing an identityquestionnaire, satisfaction test form sheets and interviews with foodservice parties. The results showed thatthe food delivery system at Tebuireng Islamic Boarding School in Jombang in East Java was already goodin management, service, and workflow but there were still shortages, such as the proportion of students andcatering service staff that was not appropriate, there was no calculation of individual student needs, and foodhandlers hygiene knowledge still needs to be improved. The level of satisfaction of students to the overallmenu of students with a thin nutritional status of 76.36% with the category “Satisfied”; students with normalnutritional status of 67.79% with the category “Dissatisfied”; and students with fat nutritional status of64.49% with the category “Dissatisfied”. Training regarding sanitation and hygiene is good and right duringthe process of providing food and training on how to process various kinds of menus from one food item.